Effects of activated charcoal on physical and mechanical properties of microwave dewaxed investment casting moulds - Yahaya, Bashir (Elsevier Ltd, 2016)
Dewaxing processes are crucial to investment casting. But the processes currently in use required series of steps that consume a lot of time (e.g. steam production in an autoclave and preheating in furnace systems). Ceramic moulds should meet required strength, porosity, collapsibility and reliability. The aim of the research is to study the effects of increasing activated charcoal content on dewaxing time and moulds properties. Ceramic moulds were prepared using modified coarse back-up stucco that was applied to the layers 3-6 only. The modified stucco was prepared by mixing with 0-30% activated charcoal. The moulds were dewaxed in microwave dewaxing test rig and then fired. During dewaxing, it was found that moulds with 30% activated charcoal usually crack on their edges. The green and fired moulds were tested for density, porosity and strength. Weibull analysis was conducted on the strength data for moulds with 0% and 25% activated the charcoal content. The dewaxing time reduced by about 37.5%, density and flexural strength of the both green and fired samples decreased for 25% increase in activated charcoal content. Whereas the porosity increase in both samples for the corresponding increase in activated charcoal content. The Weibull analysis shows a narrower strength distribution at 25% activated charcoal content. Lastly, the findings of this research show that increasing activated charcoal content in the moulds improves microwave absorption and decrease dewaxing time with no preheating required. Furthermore, porosity and collapsibility of the mould improve, while moulds strength and density decreased.